Local structure modulation via cation compositional regulation for durable Li-rich layered cathode materials. (10th May 2021) - Chen, Zaijun; Meng, Junxia; Wang, Yuqin; Ma, Quanxin; Lai, Fulin; Li, Zhifeng; Zhang, Qian; Li, Dong; Zhong, Shengwen
Abstract: A series of manganese-based lithium-rich layered oxide (LLO) cathode materials with different local structures have been synthesized by adjusting the stoichiometric ratios of Mn/Ni. One of the as-synthesized cathode materials with an Mn/Ni ratio of 7 to 2 (Li1.3 Mn0.7 Ni0.2 Co0.1 O2.4, denoted as MNC-721) showed an appropriate degree of cation mixing, thereby exhibiting superior cycling stability, better rate capability, and much slower voltage decay when compared with the other two cathode materials with different Mn/Ni ratios. More importantly, a full cell was assembled using the MNC-721 cathode material and it rendered mass-energy density retention of 90.0% after 300 cycles. An appropriate amount of mixing of the Li + ions and the transition metal (TM) in the Li layers improved the electrochemical performance of the material. The TM ions in the lithium layers can support the layered structure as well as weaken the repulsion between neighboring oxygen layers during processes of charge and discharge. The proposed method in this project is promising to be used to improve LLO cathode materials' electrochemical performance by modifying their local structures, thereby promoting their further practical applications in Li-ion batteries with high performance.